2019
DOI: 10.1080/13569775.2019.1690210
|View full text |Cite
|
Sign up to set email alerts
|

Exploring citizen turnout and invalid voting in Indonesia: two sides of the same coin?

Abstract: Exploring citizen turnout and invalid voting in Indonesia: Two sides of the same coin?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Recently, corruption has also been used as a proxy for protest in voting models, because a belief that politics is rigged can easily trigger antagonistic political behavior such as invalid voting. Generally, high perceptions of political corruption among government officials can hinder the efforts of political elites to bring people to the polls if they are perceived as insincere (Fossati and Martinez i Coma 2020). In terms of a direct relationship, the literature has found that at the aggregate level higher perceived corruption levels increase invalid ballots under compulsory voting (Martinez i Coma and Werner 2019).…”
Section: Conceptualization Research Questions and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, corruption has also been used as a proxy for protest in voting models, because a belief that politics is rigged can easily trigger antagonistic political behavior such as invalid voting. Generally, high perceptions of political corruption among government officials can hinder the efforts of political elites to bring people to the polls if they are perceived as insincere (Fossati and Martinez i Coma 2020). In terms of a direct relationship, the literature has found that at the aggregate level higher perceived corruption levels increase invalid ballots under compulsory voting (Martinez i Coma and Werner 2019).…”
Section: Conceptualization Research Questions and Hypothesesmentioning
confidence: 99%
“… 2 Beyond Latin America, in Indonesia, there always was a natural association between invalid voting and protest participation (Fossati and Martinez i Coma 2020), and in Spain’s Basque province, blank/null ballots can be directly traced to protest mobilization because local organizations explicitly called for invalid voting among sympathizers (Superti 2020). …”
Section: Notesmentioning
confidence: 99%
“…At the end of the 1990s, against the backdrop of a devastating economic crisis, massive student-led protests forced President Suharto's resignation, and Indonesia began its transition from a stable authoritarian regime to one of the world's most vibrant multi-party democracies. Indonesians quickly embraced their new democratic system: electoral participation has been among the highest in the region (Fossati and Martinez i Coma, 2020), a vibrant associational life has ensured high levels of civic engagement (Lussier and Fish, 2012) and survey research has generally found high levels of democratic support (Mujani et al, 2018).…”
Section: Polarization People and Democratic Decline In Indonesiamentioning
confidence: 99%
“…Yet this deficit is unjustified as both can fruitfully be examined in a single analytical framework. 44 Invalid (usually blank and/or null) votes often constitute a non-trivial share of all votes cast in elections, and their presence does not bode well for the democratic legitimacy of the election. They are a heterogenous group that may result from different causal pathways depending on whether it is the voter or the electoral authority that invalidates the ballot.…”
Section: Csoes and Invalid Votingmentioning
confidence: 99%